Avaliação da qualidade do sono em pessoas idosas participantes do projeto vida ativa-UFT - Formiga, Adriane Borges (Universidade Federal do Tocantins, 2024)
Sleep quality is na extremely important aspect to be assessed, especially for the elderly. The present study aimed to evaluate the prevalence of sleep quality among elderly people participating in the Active Life project. This is a field-based, cross-sectional and quantitativequalitative study. The recruitment of participants was done by non-probabilistic sampling through a direct invitation to the Active Life Project – UFT, and included 11 eligible elderly people, 8 females and 3 males. The analyses were processed using the Statistical Package for the Social Sciences - SPSS® version 20.0 for Windows®, considering a significance value of p <0.05. The results concluded that the elderly people participating in the Active Life (UFT) project had "good" sleep quality.